AUTOMATED CYBER THREAT INTRUSION DETECTION WITH HYPER PARA OPTIMIZATION - Dayanidhy, M.; Pooja, M.; Pavithira, M.; Adhithyaa, T.; Karthikeyan, K.; Manikandan, K.; Mahendran, R. (International Journal of Psychosocial Rehabilitation, 2020)
Technology has presented many security frameworks in which IoT focused surveillance system is more populous. Sensors and cameras serve as backbone of the network for many security purposes and is merely an alarming device that senses movement. Now the technology is becoming meaningless. In the this article we introduced and applied an integrated Internet of Things (IoT) protection framework that operates on a concepts of Global System for Mobile Communication (GSM) tech in an attempt to control crime in stores, malls, etc. This system is an innovative surveillance device that uses CCTV cameras not only constantly recording, but also capturing images when movement sensors sense movement. Passive Infrared (PIR) sensor is used for motion detection. The captured image is then sent to the owner and to a nearby police patrol through SMS along with the location. In the meantime, toxic chemicals are pumped to keep the burglar from escaping the store, which would leave him helpless for a certain amount of time. The engineered device will also produce annoying sonic influencer-generated sound.